2006
DOI: 10.1007/s11274-006-9138-0
|View full text |Cite
|
Sign up to set email alerts
|

Repeated batch cultivation of the microalga Spirulina platensis

Abstract: The cultivation of photosynthetic microorganisms such as the microalga Spirulina platensis can provide an alternative source of food. The water in Mangueira Lagoon (Rio Grande do Sul state, southern Brazil) has several required nutrients for the growth of Spirulina and could be added to culture medium to reduce the cost of producing S. platensis. Although little studied, repeated batch cultivation is a very useful technique because it has a better cost-benefit ratio than other cultivation methods. In a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…The growth profile of Spirulina platensis LEB‐52 in 20 % ZM presented a stationary phase from the 24 th to the 30 th d of cultivation, followed by a death phase after the 33 rd d. Andrade and Costa reported a decrease in the concentration of Spirulina platensis LEB‐52 biomass after the 30 th d when cultivated in 20 % ZM (diluted with distilled water). The values obtained in the literature for µ max of Spirulina platensis LEB‐52 cultivated in 100 % ZM were on the order of 0.034 to 0.111 1/d, and on the order of 0.06 to 0.12 1/d for 20 % ZM, under conditions similar to those used in the present study.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The growth profile of Spirulina platensis LEB‐52 in 20 % ZM presented a stationary phase from the 24 th to the 30 th d of cultivation, followed by a death phase after the 33 rd d. Andrade and Costa reported a decrease in the concentration of Spirulina platensis LEB‐52 biomass after the 30 th d when cultivated in 20 % ZM (diluted with distilled water). The values obtained in the literature for µ max of Spirulina platensis LEB‐52 cultivated in 100 % ZM were on the order of 0.034 to 0.111 1/d, and on the order of 0.06 to 0.12 1/d for 20 % ZM, under conditions similar to those used in the present study.…”
Section: Resultssupporting
confidence: 83%
“…The main studies on the autotrophic production of biomass by Spirulina platensis LEB‐52 used Zarrouk's medium in the following forms: non‐diluted (100 %), diluted to 60 %, diluted to 50 %, diluted to 20 %, and diluted to 10 % (v/v), with the dilutions made from Mangueira Lagoon water (MLW). However, there are also studies that used tap water to dilute the ZM .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers [33] and [19] have reported that the microalgal species Chlorococcum littorale could grow under CO 2 concentrations of over 20 Chlorella sp. were able to grow up even in aeration containing CO 2 up to 40%, at culture pH as low as 4 [36].…”
Section: Carbon Dioxide Fixation In Photosynthetic Processmentioning
confidence: 99%
“…Shorter duplication time is preferred for the mass cultivation. As the duplication time increases the speed of the cell duplication decreases and this causes the commercial cultivation to become non profitable (Reinehr and Costa, 2006). The duplication time reported by Vonshak (1997) for the A. platensis M2 strains grown in 0.5 M NaCl treatment (t d = 0.663 days).…”
mentioning
confidence: 99%